A time-saving method to assess power output at lactate threshold in well-trained and elite cyclists - Støren, Ø.; Rønnestad, B. R.; Sunde, A.; Hansen, J.; Ellefsen, S.; Helgerud, J. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to examine the relationship between lactate threshold (LT) as a percentage of maximal oxygen consumption (VO2max) and power output at LT (LTW) and also to investigate to what extent VO2max, oxygen cost of cycling (CC), and maximal aerobic power (MAP) determine LTW in cycling to develop a new time-saving model for testing LTW. To do this, 108 male competitive cyclists with an average VO2max of 65.2 ± 7.4 ml/kg/min and an average LTW of 274 ± 43 W were tested for VO2max, LT %VO2max, LTW, MAP, and CC on a test ergometer cycle. The product of MAP and individual LT in %VO2max was found to be a good determinant of LTW (R = 0.98, p < 0.0001). However, LT in %VO2max was found to be a poor determinant of LTW (R = 0.39, p < 0.0001). Based on these findings, we have suggested a new time-saving method for calculating LTW in well-trained cyclists. The benefits from this model come both from tracking LTW during training interventions and from regularly assessing training status in competitive cyclists. Briefly, this method is based on the present findings that LTW depends on LT in %VO2max, VO2max, and CC and may after an initial test session reduce the time for the subsequent testing of LTW by as much as 50% without the need for blood samples.